CULTURAL INFLUENCES IN ACEH PEMULIA JAMEE CUISINE - Fida wati (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This qualitative research provides solutions and information in the knowledge of intercultural local wisdom in Aceh. the relationship between diverse cultural phenomena in food that is collaborated on Acehnese culture. The purpose of this study is to explain the knowledge and information about Acehnese culinary fusion that shows the history, creativity, and resilience of the island. Each bite tells a story of cultural exchange, adaptation, and the power of food to unite traditions. A prime example of how diverse cultural influences combine to create a vibrant culinary tradition. Jamaican culinary culture reflects its rich history of colonization, migration, and trade, drawing on Indigenous, African, European, Indian, Chinese, and Middle Eastern influences. Its cuisine relies heavily on strong and aromatic spices such as pimento, nutmeg, thyme, and Scotch bonnet peppers, which blend with a variety of culinary styles. From grilling (Indigenous) to steaming (Chinese), Acehnese cooks adapt methods from various cultures to suit local ingredients. The multicultural community encourages innovation and collaboration in the kitchen. This fusion is implemented at a gathering for jamee breeders. This tradition is a legacy from our ancestors to provide the best hospitality for guests